Carbon monoxide levels in the expired air of smokers - Türkcan, Ahmet; Çakmak, Duran (Journal of Dependence, 2004)
Objective: There are a variety of independent methods of estimating smoking status. The measurement of carbon monoxide in the expired air has proven to be a reliable and convenient method. The purpose of this study is to determine the optimal breath carbon monoxide concentration cut-off level to distinguish actual smokers from nonsmokers.Method: A hand held breath analyzer (Micro CO) was used to measure expired-air carbon-monoxide concentrations. Breath carbon monoxide levels were measured in 31 smokers and 30 nonsmokers.Results: The range of carbon monoxide concentrations obtained was 0-5 parts per million (ppm) in the non-smoking group and 5-70 ppm in the smoking group. Smokers had a mean breath carbon monoxide concentration of 27.8 + 17.0 ppm and non-smokers had a mean of 1.7 +1.0 ppm (p
Keywords: Carbon monoxide; smokers; nonsmokers